Major cardiovascular events and associated factors among routine hemodialysis patients with end-stage renal disease at tertiary care hospital in Somalia - Farah Yusuf Mohamud, Mohamed; Nur Adan, Faduma; Osman Omar Jeele, Mohamed; Ahmed, Mohamed A. M. (Frontiers in Medicine, 2023)
Introduction: Cardiovascular complications are the most significant cause of death in patients undergoing routine hemodialysis(HD) with end-stage renal disease(ESRD). The main objective of this study is to determine the significant cardiac events and risk factors in patients undergoing routine hemodialysis in Somalia. Method: This observational study was conducted at a dialysis center in Somalia. 200 out of 224 were included. All of them had ESRD and were on hemodialysis during the study period between May to October 2021. The records of all patients were reviewed, and the following parameters were analyzed socio-demographic factors, risk factors for cardiovascular disease, and the presence of cardiovascular diseases. Results: The mean age was 54±17.5 years (range 18–88 years), and 106(53%) patients were males. The prevalence of the cardiovascular disease among hemodialysis patients was 29.5%. Moreover, the distribution of cardiovascular diseases were different; heart failure was the most common about 27.1%, flowed by coronary artery disease(17%), pericarditis and pericardial-effusion(13.6%), dysrhythmia(10.2%), cerebrovascular-accident(8.5%), and peripheral vascular disease (3.4%).About 176(88%) participants had at least one modifiable cardiovascular risk factor. The most common modifiable cardiovascular risk factor was hypertension (n=45,25.1%), flowed by anemia(n=28, 15.6%), and diabetes (n=26, 14.5%). Younger(18-30) participants were 6 times less likely to have cardiovascular events among hemodialysis compared to older age 0.4 (0.11-1.12). Conclusion: High prevalence rate of cardiovascular complications was confirmed in ESRD patients receiving hemodialysis in the main HD center in Somalia. The significant risk factors for CVD in HD patients with ESRD include diabetes, anemia, and hypertension.